Improving care for patients whose recovery is uncertain. The AMBER care bundle: design and implementation. Issue 4 (1st December 2015) - Carey, Irene; Shouls, Susanna; Bristowe, Katherine; Morris, Michelle; Briant, Linda; Robinson, Carole; Caulkin, Ruth; Griffiths, Mathew; Clark, Kieron; Koffman, Jonathan; Hopper, Adrian
Abstract : Introduction: Despite preferences to the contrary, 53% of deaths in England occur in hospital. Difficulties in managing clinical uncertainty can result in delayed recognition that a person may be approaching the end of life, and a failure to address his/her preferences. Planning and shared decision-making for hospital patients need to improve where an underlying condition responds poorly to acute medical treatment and there is a risk of dying in the next 1–2 months. This paper suggests an approach to improve this care. Intervention: A care bundle (the AMBER care bundle) was designed by a multiprofessional development team, which included service users, utilising the model for improvement following an initial scoping exercise. The care bundle includes two identification questions, four subsequent time restricted actions and systematic daily follow-up. Clinical impact: This paper describes the development and implementation of a care bundle. From August 2011 to July 2012, 638 patients received care supported by the AMBER care bundle. In total 42.8% died in hospital and a further 14.5% were readmitted as emergencies within 30 days of discharge. Clinical outcome measures are in development. Conclusions: It has been possible to develop a care bundle addressing a complex area of care which can be a lever for cultural change. The implementation of the AMBER care bundle has the potential to improve care of clinically uncertain hospital patients who may be approaching the end of life by supporting their recognition and prompting discussion of their preferences. Outcomes associated with its use are currently being formally evaluated.